The Role of Embroidery and Ethno Interaction in Traditional Art Crafts - Khamidova Gulmira Khamidovna; Amonova Zarifa Usmonovna (Genius Publishing Group, 2022)
In our school, the types and genres of our national applied arts are taught in fine arts and technology classes. But in practice, the secrets of national embroidery are not taught. Even in our family, embroidery is still practiced in some areas. We need to develop the art of embroidery, which is our national heritage and preserve and spread our national identity around the world, from our national fabrics, our national doppies and our clothes to our shoes
Keywords: Embroidery; Aesthetic Value; Handicrafts; Applied Arts